STATISTICAL DETECTION OF BREAST CANCER BY MAMMOGRAM IMAGE - gk, Rajini; Naseera, Shaik; M, Saravanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To create awareness about the breast cancer which has become one of the most common diseases among women that leads to death if not recognized at early stage. Methods: The technique of acquiring breast image is called mammography and is a diagnostic and screening tool to detect cancer. A cascade algorithm based on these statistical parameters is implemented on these mammogram images to segregate normal, benign, and malignant diseases. Results: Statistical features - such as mean, median, standard deviation, perimeter, and skewness - were extracted from mammogram images to describe their intensity and nature of distribution using ImageJ. Conclusion: A noninvasive technique which includes statistical features to determine and classify normal, benign, and malignant images are identified. Keywords: Breast cancer, Benign, Malignant, Mammogram image, ImageJ.